Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the equation [tex]\(x^3 + 3x^2 - 5x - 15 = 0\)[/tex] for [tex]\(x\)[/tex] over the set of real numbers, we follow a structured approach to find the roots.
1. Identify the problem: We need to find the real roots of the cubic equation [tex]\(x^3 + 3x^2 - 5x - 15 = 0\)[/tex].
2. Analyze possible roots: We start by considering possible rational roots using the Rational Root Theorem, which states that any rational root of the polynomial equation, where the polynomial is in standard form [tex]\( ax^n + bx^{n-1} + ... + k = 0 \)[/tex], must be a factor of the constant term ([tex]\(-15\)[/tex]) divided by the leading coefficient (which is 1 here). So we look at the factors of [tex]\(-15\)[/tex]: [tex]\( \pm 1, \pm 3, \pm 5, \pm 15 \)[/tex].
3. Testing possible roots:
- For [tex]\(x = -3\)[/tex]:
[tex]\[ (-3)^3 + 3(-3)^2 - 5(-3) - 15 = -27 + 27 + 15 - 15 = 0 \][/tex]
Hence, [tex]\(x = -3\)[/tex] is a root.
4. Factor the polynomial using [tex]\(x = -3\)[/tex]:
We can then factor out [tex]\(x + 3\)[/tex] from the polynomial. Using polynomial division or synthetic division, we divide [tex]\(x^3 + 3x^2 - 5x - 15\)[/tex] by [tex]\(x + 3\)[/tex]:
[tex]\[ (x^3 + 3x^2 - 5x - 15) \div (x + 3) = x^2 - 5 \][/tex]
Thus, we have:
[tex]\[ x^3 + 3x^2 - 5x - 15 = (x + 3)(x^2 - 5) \][/tex]
5. Solve the quadratic equation [tex]\( x^2 - 5 = 0 \)[/tex]:
- Set [tex]\( x^2 - 5 = 0 \)[/tex]:
[tex]\[ x^2 - 5 = 0 \][/tex]
[tex]\[ x^2 = 5 \][/tex]
[tex]\[ x = \pm\sqrt{5} \][/tex]
6. Combine all solutions:
From the steps above, we have found that the solutions to the equation [tex]\(x^3 + 3x^2 - 5x - 15 = 0\)[/tex] are:
[tex]\[ x = -3, \sqrt{5}, -\sqrt{5} \][/tex]
Therefore, the exact solutions over the set of real numbers are:
[tex]\[ x = -3, \sqrt{5}, -\sqrt{5} \][/tex]
1. Identify the problem: We need to find the real roots of the cubic equation [tex]\(x^3 + 3x^2 - 5x - 15 = 0\)[/tex].
2. Analyze possible roots: We start by considering possible rational roots using the Rational Root Theorem, which states that any rational root of the polynomial equation, where the polynomial is in standard form [tex]\( ax^n + bx^{n-1} + ... + k = 0 \)[/tex], must be a factor of the constant term ([tex]\(-15\)[/tex]) divided by the leading coefficient (which is 1 here). So we look at the factors of [tex]\(-15\)[/tex]: [tex]\( \pm 1, \pm 3, \pm 5, \pm 15 \)[/tex].
3. Testing possible roots:
- For [tex]\(x = -3\)[/tex]:
[tex]\[ (-3)^3 + 3(-3)^2 - 5(-3) - 15 = -27 + 27 + 15 - 15 = 0 \][/tex]
Hence, [tex]\(x = -3\)[/tex] is a root.
4. Factor the polynomial using [tex]\(x = -3\)[/tex]:
We can then factor out [tex]\(x + 3\)[/tex] from the polynomial. Using polynomial division or synthetic division, we divide [tex]\(x^3 + 3x^2 - 5x - 15\)[/tex] by [tex]\(x + 3\)[/tex]:
[tex]\[ (x^3 + 3x^2 - 5x - 15) \div (x + 3) = x^2 - 5 \][/tex]
Thus, we have:
[tex]\[ x^3 + 3x^2 - 5x - 15 = (x + 3)(x^2 - 5) \][/tex]
5. Solve the quadratic equation [tex]\( x^2 - 5 = 0 \)[/tex]:
- Set [tex]\( x^2 - 5 = 0 \)[/tex]:
[tex]\[ x^2 - 5 = 0 \][/tex]
[tex]\[ x^2 = 5 \][/tex]
[tex]\[ x = \pm\sqrt{5} \][/tex]
6. Combine all solutions:
From the steps above, we have found that the solutions to the equation [tex]\(x^3 + 3x^2 - 5x - 15 = 0\)[/tex] are:
[tex]\[ x = -3, \sqrt{5}, -\sqrt{5} \][/tex]
Therefore, the exact solutions over the set of real numbers are:
[tex]\[ x = -3, \sqrt{5}, -\sqrt{5} \][/tex]
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.